2016
DOI: 10.1001/jamadermatol.2015.3775
|View full text |Cite
|
Sign up to set email alerts
|

Association of Patient Risk Factors and Frequency of Nevus-Associated Cutaneous Melanomas

Abstract: The reported frequencies of associations between primary cutaneous melanomas and melanocytic nevi vary widely between 4% and 72%. However, earlier histopathologic studies were limited by their retrospective design and did not assess the influence of important patient-related risk factors. OBJECTIVES To identify the frequency of nevus-associated melanomas and correlate patientand melanoma-related factors. DESIGN, SETTING, AND PARTICIPANTS A prospective, single-center, observational study with systematic documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 34 publications
9
86
1
3
Order By: Relevance
“…17,19 One study 20 found that patients with multiple primary melanomas or a family history of melanoma had fewer nevusassociated melanomas than patients with high nevus counts. For these reasons, people with many nevi may be most likely to benefit from sequential digital dermoscopy and total body photography for ongoing surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…17,19 One study 20 found that patients with multiple primary melanomas or a family history of melanoma had fewer nevusassociated melanomas than patients with high nevus counts. For these reasons, people with many nevi may be most likely to benefit from sequential digital dermoscopy and total body photography for ongoing surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…An individual with a single clinically dysplastic naevus has a twofold increased risk for melanoma, whereas having greater than 10 clinically dysplastic naevi is associated with a 12-fold increased risk [104] . For each additional naevus on the body, relative risk of CMM increases by 3% [105] and newly published work indicates that over 50% of CMM arise from naevi [106] , but this remains to be confirmed in larger studies. Dysplastic naevi are more common in patients with melanoma, and a personal and family history of melanoma can significantly increase the incidence of finding dysplastic naevi in a patient.…”
Section: Naevi and Melanomamentioning
confidence: 95%
“…Melanoma often arises from melanocytic nevi (i.e. moles) (4), which frequently are found on sun-exposed areas (5). Ultraviolet (UV) radiation in sunlight (6) or from tanning beds (7) is the major environmental risk factor for melanoma.…”
Section: Introductionmentioning
confidence: 99%